Proceedings of the 1st Engineering Data Analytics and Management Conference (EAMCON 2025) - Tanweer Ali; Nitesh Naik; Saad Hassan Kiani (Atlantis Press International BV, 2025)
This open access volume presents the select peer-reviewed proceedings of the 1st Engineering Data Analytics and Management Conference.